Edukasi Perilaku Merokok Pada Remaja di Kelurahan Pasie Nan Tigo Kecamatan Koto Tangah - Sari, Putri Minas; Dafriani, Putri; Resta, Harinal Afri; Diana Morika, Honesty (Jurnal Abdimas Saintika, 2021)
Smoking behavior is a problem, both environmentally and individually, and the incidence is quite high in Padang City, especially in Pasie Nan Tigo Village, Koto Tangah District. It can be seen from the data on visits to the puskesmas with complaints of breathlessness and coughing due to smoking, most of the smoking perpetrators were teenagers as much as 70% of 100%. The occupation population of adolescents is mostly fishermen and smoking is mandatory when they are working or at home. Based on these problems, the purpose of this community service is to provide education about smoking behavior in adolescents using extension methods. The results obtained were that there was an increase in the participants' knowledge about the dangers of smoking after counseling. The conclusion is that counseling can increase adolescent knowledge about the dangers of smoking so that it is expected to also influence adolescent behavior to be able to quit smoking. Keywords: Smoking, Health Education, knowledge